2019
DOI: 10.1016/j.ejvs.2018.12.032
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Study Comparing WBC scan and 18F-FDG PET/CT in Patients with Suspected Prosthetic Vascular Graft Infection

Abstract: WHAT THIS PAPER ADDS This study is the second and the largest to compare 18 F-fluoro-D-glucose (FDG) positron emission tomography/ computed tomography (PET/CT) and white blood cell scan in the diagnosis of prosthetic vascular graft infections (PVGIs). The white blood cell scan was more accurate than 18 F-FDG PET/CT. Moreover, there was only one false negative 18 F-FDG PET-CT result under antibiotic therapy. Nuclear imaging results should be included in the diagnostic criteria for prosthetic vascular graft infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
20
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 18 publications
0
20
0
2
Order By: Relevance
“…In this study, CT showed high number of false negative scans both in early infections, where the findings were wrongly interpreted as post-surgical changes, and in late infections, where CT did not show any alteration [ 43 ]. In another recent comparative study by Puges et al, radiolabelled WBC scan showed higher accuracy than [ 18 F]FDG PET/CT, even in patients under antibiotic treatment and in thrombosed graft infection [ 44 ].…”
Section: Consensus Statementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, CT showed high number of false negative scans both in early infections, where the findings were wrongly interpreted as post-surgical changes, and in late infections, where CT did not show any alteration [ 43 ]. In another recent comparative study by Puges et al, radiolabelled WBC scan showed higher accuracy than [ 18 F]FDG PET/CT, even in patients under antibiotic treatment and in thrombosed graft infection [ 44 ].…”
Section: Consensus Statementsmentioning
confidence: 99%
“…For this PICO, 73 papers were retrieved but only 3 studies were finally selected [ 22 , 43 , 44 ]. However, no studies directly comparing patients with and without antibiotic treatment for VGEI exist.…”
Section: Consensus Statementsmentioning
confidence: 99%
“…Jak zmíněno výše, přínos FDG PET/CT v diagnostice infekce chirurgických cévních náhrad byl hodnocen řadou studií. [18][19][20][21][22][23][24][25][26][27][28][32][33][34][35][36][37] Separátní data, která by analyzovala přínos FDG PET/CT v diagnostice infekcí stentgraftu (SGI) po EVAR, jsou však v literatuře vzácná, výše uvedené studie jsou provedeny na populacích výhradně s chirurgickými protézami, popř. na populacích smíšených (tedy pacientů s VG spolu s pacienty po EVAR), extrahovat údaje o SGI lze jen výjimečně (např.…”
Section: Záněty Cévních Náhrad a Stentgraftůunclassified
“…V přímém porovnání diagnostické přesnosti FDG PET/CT a WBC na smíšeném kolektivu vykázala WBC pro diagnózu VGI signifi kantně vyšší diagnostickou přesnost. 37 Parametry diagnostické přesnosti při "per--graft" analýze byly při porovnání FDG PET/CT vs. WBC: senzitivita 85 % vs. 90 % a specifi cita 68 % vs. 91 %. V práci Erba a spol.…”
Section: Záněty Cévních Náhrad a Stentgraftůunclassified
“…Which statements are correct among the following regarding the radiological diagnosis of prosthetic vascular graft infection (PVGI)? 14 A. Computed tomography angiography (CTA) has a good sensitivity in low-grade infections B. Nuclear imaging exams should be performed first, before CTA C. 18F-FDG PET/CT has a good specificity for infections diagnosis D. White blood cell scan has a better accuracy than 18F-FDG PET/CT for PVGI diagnosis E. Positive 18F-FDG PET/CT results should be interpreted with caution in thrombosed grafts.…”
mentioning
confidence: 99%